Hubungan Ketepatan Penulisan Diagnosis Penyakit dengan Keakuratan Kode Diagnosis pada Pasien Rawat Inap di Rumah Sakit - Endang Sri Dewi Hastuti Suryandari; Regina Novi Rahmadhani; Acmad Zani Pitoyo; Hartaty Sarma Sangkot; Avid Wijaya (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
The accuracy of the disease diagnoses code is determined by the accuracy of writing the diagnoses. The result of observation in 10 inpatient medical record documents at the TNI-AD 05.08.04 Hospital Lawang, 5 documents were found with inaccurate codes (50%) with 3 incorrectly written diagnoses. The purpose of this study was to analyze the effect of the accuracy in writing disease diagnoses to the accuracy of the diagnoses code for inpatients at the TNI-AD 05.08.04 Hospital, Lawang. This methode of research was an analytic observational with a cross-sectional approach. The number of sample analyze were 100 inpatient medical record documents which hospitalitaion from March to August 2022 and using simple random sampling technique by lottery. The accuracy of writing diseases diagnoses of inpatient was an independent variable and the accuracy of the diagnoses code for the inpatient at the TNI-AD 05.08.04 Hospital, Lawang was dependent variable in this study. The results showed the accuracy in writing disease diagnoses was 70% and the accuracy of the disease diagnoses code was 45%. The analytic test with Chi Square showed significantly the effect of accuracy in writing diseases diagnoses to the accuracy of diagnoses code for inpatient at the TNI-AD 05.08.04 Hospital Lawang with a p-value = 0.000 (<0.05). The accuracy in writing diseases diagnoses by doctor that refer to medical terminology of ICD-10 will producted an accurate diagnoses codes.